Dexamethasone Preconditioning Improves the Response of Collagen-Induced Arthritis to Treatment with Short-Term Lipopolysaccharide-Stimulated Collagen-Loaded Dendritic Cells - Corina Peña; David Gárate; Juan Contreras-Levicoy; Octavio Aravena; Diego Catalán; Juan C. Aguillón (Clinical and Developmental Immunology)
Background. Pharmacologically modulated dendritic cells (DCs) have been shown to restore tolerance in type II collagen-(CII-) induced arthritis (CIA). We examined the effect of dexamethasone (DXM) administration as a preconditioning agent, followed by an injection of lipopolysaccharide-(LPS-) stimulated and CII-loaded DCs on the CIA course. Methods. After CIA induction, mice pretreated with DXM were injected with 4-hour LPS-stimulated DCs loaded with CII (DXM/4hLPS/CII/DCs). Results. Mice injected with DXM/4hLPS/CII/DCs displayed significantly less severe clinical disease compared to animals receiving 4hLPS/CII/DCs alone or those in which only DXM was administered. Cytokine profile evaluation showed that CD4+ T cells from DXM/4hLPS/CII/DCs and 4hLPS/CII/DCs groups release higher IL-10 levels than those from mice receiving DXM alone or CIA mice. CD4+ T cells from all DC-treated groups showed less IL-17 release when compared to the CIA group. On the contrary, CD4+ T cells from DXM/4hLPS/CII/DCs and 4hLPS/CII/DCs groups released higher IFN-γ levels than those from CIA group. Conclusion. A combined treatment, including DXM preconditioning followed by an inoculation of short-term LPS-stimulated CII-loaded DCs, provides an improved strategy for attenuating CIA severity. Our results suggest that this benefit is driven by a modulation in the cytokine profile secreted by CD4+ T cells.